Avaliação da autoestima e depressão após cirurgia bariátrica - Bressan, Jurema de Andrade (2017)
Introduction: After bariatric surgery, social, behavioral, and eating habits must change. The lack of psychological monitoring may affect negatively the adaptation to the new body image and lifestyle, and result in low self-esteem and depressive symptoms. Objective: To evaluate the effects of bariatric surgery on accepting a new body image and the processes of self-esteem and depression in postoperative patients. Methods: This was a Cross-sectional study on patients who underwent bariatric surgery from 2015 to 2016 at a hospital in southern Brazil. After approval by the Ethics Committee, each consenting patient was interviewed by phone. Sociodemographic and clinical data were collected, and the electronic medical records were examined. Depressive symptoms were identified by using the Beck Inventory, and self-esteem was measured by the Rosenberg Self-Esteem Scale. Results: Seventy-one patients (76.1% women) participated, with a mean age of 39.8±10.3 years. The majority were married (77.5%), had a high education level (54.9%), presence of comorbidities (62.0%), and anxiety symptoms (59.2%). Before surgery, 9.9% had depressive symptoms, which increased to 38% after surgery, according to the following breakdown: 3.3% severe, 8.3% moderate to severe, and 26.7% mild to moderate. Anxiety symptoms were associated with the use of antidepressants (p = 0.003) and shorter postoperative time (p = 0.013). The majority (98.4%) presented a moderate self-esteem score. There was a significant reduction in body weight and body mass index after the bariatric surgery (p <0.001). Conclusion: The findings revealed a moderate self-esteem and increased depressive symptoms as a result of bariatric surgery.